Heart Failure : A Comprehensive Guide to Pathophysiology and Clinical Care - Eisen, Howard (Springer London : Imprint: Springer, 2017)
This book elucidates the etiology of heart failure (HF) to assist understanding in the clinical therapies available. It explains these in light of the better understanding of the pathophysiology of HF, which has translated into dramatic improvements in patient outcome. The chapters detail the causes, diagnosis and treatment of HF, and recognize that having become the leading cause of morbidity, mortality and hospitalization in the developed world, even patients with the most advanced HF have options that allow prolonged survival. This includes alternatives to cardiac transplantation, including mechanical circulatory support with a rapidly growing number of new, smaller, more reliable devices becoming available. Heart Failure: A Comprehensive Guide to Pathophysiology and Clinical Care will be critical reading for all involved in the management of these patients and provides a scientific and clinical reference for trainees in cardiovascular disease as well as physicians involved in caring for these patients.- Resumé vydavatel